Entrepreneurial strategies for development of family businesses and small and medium scale enterprises in Nigeria - Nkechi, Apaokueze Tessy; Chukwuka, Ernest Jebolise; Peter, Abude; Solomon, Egbule, A. C,; bieze, Ewere Success O; Victor, Uwujaha (Edelweiss Applied Science and Technology, 2025)
This study examines the entrepreneurial strategies employed by small and medium-sized enterprises (SMEs) in Delta State, Nigeria, and their impact on business growth and sustainability. SMEs are recognized as crucial drivers of economic development, contributing significantly to employment generation, poverty reduction, and local economic diversification. However, despite their potential, SMEs in Delta State face various challenges, including inadequate financing, poor infrastructure, and limited market access. The study utilized a descriptive survey research design, targeting 300 SMEs across various sectors, including agriculture, manufacturing, and services. Data was collected through questionnaires administered to owners, managers, and key personnel of the SMEs. The findings revealed that SMEs in Delta State adopt several entrepreneurial strategies, such as competitive pricing, product diversification, technological adoption, and collaboration with other businesses. These strategies have significantly contributed to business growth, enhanced profitability, expanded market reach, and improved competitiveness. However, challenges such as limited access to financing, poor infrastructure, regulatory barriers, and high operational costs hinder the full implementation of these strategies. Based on the findings, the study recommends increased access to affordable financing, improved infrastructure, supportive government policies, and enhanced training programs to foster SME sustainability in the region. The study concludes by emphasizing the importance of strategic entrepreneurial initiatives in driving the growth of SMEs, suggesting that policymakers, entrepreneurs, and researchers work collaboratively to address the challenges faced by SMEs in Delta State.